Correlation between preoperative remaining kidney volume and chronic kidney disease after donor nephrectomy - Leenanupunth, Charoen; Hajidae, Malik; Phongkitkaru, Sith (Insight Urology, 2019)
Objective: The aim of this study was to evaluate whether preoperative remaining kidney volume correlates with renal function after a donor nephrectomy. Material and Method: A total of 303 kidney donors who underwent donor nephrectomies at Ramathibodi Hospital in Bangkok, Thailand between January 2011 and December 2015 were retrospectively reviewed. The donors’ preoperative kidney volumes were calculated from computed tomography angiographies of the renal artery. Each donor’s demographic data, surgical approach (open/laparoscopic), donated kidney side (right/left), and post-operative renal function (creatinine level and eGFR) were collected and analyzed between the two groups. Result: Seventy of the living kidney donors developed CKD. There were no statistical differences in the donated kidney side (p=0.371), surgical approach (p=0.549), donated kidney volume (p=0.087), donated kidney volume percentage (p=0.126), remaining kidney volume percentage (p=0.126), weight (p=0.056), height (p=0.355), and body mass index (BMI) (p=0.062) between the two groups. The donor age medians in the CKD group and non-CKD group were 48 years old [interquartile range (IQR)=42-53] and 35 years old (IQR=29-44), respectively. The mean preoperative remaining kidney volumes in the CKD group and non-CKD group, respectively, were 114.6 ml [standard deviation (SD)=16.6] and 122.2 ml (SD=21.1). There were statistically significant differences in age (p=0.000), gender (p=0.001), and preoperative remaining kidney volume (p=0.002) between the two groups. Multivariate analysis showed that gender, age, BMI, and remaining kidney volume exhibited significant odds ratios (OR=8.971, 1.109, 1.167, and 0.973, respectively); therefore, all of these variables were predictive risk factors for the development of CKD after a donor nephrectomy at the 1-year follow-up. Conclusion: Preoperative remaining kidney volume, age, gender, and BMI were found to be correlated with CKD after a donor nephrectomy at the 1-year follow-up.